Tissue-resident memory T cells in urinary tract diseases - Xu, Guofeng; Li, Yuying; Lu, Guanting; Xie, Daoyuan (Frontiers in Immunology, 2025)
Tissue-resident memory T (TRM) cells are a specialized subset of memory T cells that permanently reside in non-lymphoid tissues, providing localized and long-lasting immune protection. In the urinary tract, TRM cells play critical roles in defending against infections, mediating tumor immunity, and influencing the pathogenesis of chronic inflammatory diseases. Their therapeutic potential is immense, with promising avenues for vaccine development, enhanced cancer immunotherapy, and targeted treatments for chronic inflammation. However, challenges remain in harnessing their protective roles while minimizing their pathological effects, particularly in immunosuppressive or inflammatory microenvironments. This review explores the diverse roles of TRM cells in urinary tract diseases, including infections, cancer, and chronic inflammation, and discusses therapeutic strategies and future directions for leveraging TRM cells to improve clinical outcomes. By advancing our understanding of TRM cell biology, we can develop innovative interventions that balance their immune-protective and regulatory functions.